MOTIF, BENTUK, KOMPOSISI DAN MAKNA BATIK DI KABUPATEN TEBO PROVINSI JAMBI - Yuliana Wulandari; Minarsih .; Ajusril . (Universitas Negeri Padang, 2012)
Abstract The purpose of this study were to (1) describe about form motif which there is on batik Tebo, (2) describe about composition motif which there is on batik Tebo, (3) describe about meaning motif which be contained on motif batik Tebo. The data of this study is the motif Tebo. The data source of this research is primary data and secondary data were spoken directly by informants as the original speakers. Data collected by the data collection techniques used were observation (observation), interviews and documentary study. The findings of the study are five Tebo batik motifs rebung nyengum, bambu runcing, bungo muko macan, serat kayu rengas and sialang rajo. Kata kunci: Motif, Bentuk, Komposisi, Makna Batik,Tebo